Analysis of U.S. theme park selection and international implications. Issue 1 (2nd January 2018) - Pan, Haoyuan; Bahja, Frida; Cobanoglu, Cihan
ABSTRACT: Theme parks face stiff competition in local and international markets. Theme parks tend to create competitive advantages in the market by investing in different factors which influence visitors' selection of a theme park. Theme parks attract visitors from all nationalities. The purpose of this study was to explore six influencing factors on U.S. theme park visitors' choice that can be applicable in different geographic positioning parks. A choice-based conjoint (CBC) model was designed with respective levels for six considered influencing factors: type of park, price, distance from accommodation, children friendly, and online reviews. The findings revealed that online reviews were the most important relative factor followed closely by price and type of theme park. The other factors shared a lower relative importance. CBC analysis results generated the best and the worst profile for theme parks, which can serve as a guide theme park managers as they invest and plan strategically for success. Results of this study of U.S. parks but as theme parks are targeted toward similar populations the results could have implications internationally.